1977
DOI: 10.1210/endo-100-4-918
|View full text |Cite
|
Sign up to set email alerts
|

Insensitivity of Bonnet Monkeys to (D-Ala6, Des-Gly10) LHRH Ethylamide, a Potent New Luteinizing Hormone Releasing Hormone Analogue in Rats and Mice

Abstract: The Luteinizing Hormone Releasing Hormone (LHRH) activity of (D-Ala6, Des-Gly10) LHRH ethylamide was compared with that of LHRH in oöphorectomized bonnet monkeys by determining serum LH and FSH concentrations at various time intervals after a sc injection of 100 mug of LHRH and either 100 mug or 1 mg of the analogue. Following administration of synthetic LHRH, a significant rise in both serum LH and FSH was observed. In contrast, no discernible change in serum gonadotropin concentrations was noted following in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It has been reported that rhesus monkeys and mice are relatively resistant to the anti-testicular effects of GnRH agonists (Vickery, 1981;Bex, 1982). The only study carried out in bonnet monkeys reported that bonnet monkeys are less sensitive to GnRH (Levitan et al, 1977). However, in an earlier communication we have reported that bonnet monkeys respond very well to GnRH injection.…”
Section: Discussionmentioning
confidence: 73%
“…It has been reported that rhesus monkeys and mice are relatively resistant to the anti-testicular effects of GnRH agonists (Vickery, 1981;Bex, 1982). The only study carried out in bonnet monkeys reported that bonnet monkeys are less sensitive to GnRH (Levitan et al, 1977). However, in an earlier communication we have reported that bonnet monkeys respond very well to GnRH injection.…”
Section: Discussionmentioning
confidence: 73%
“…To establish the mechanism of the peptide carrier action, the influence of a highly active luliberin agonist alarelin [24] and peptide-DNA ratio on the efficiency of pCMVluc plasmid transfer in human hepatocarci noma cells HepG2 was investigated (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that the non-human primate is less sensitive to GnRH administration than the rodent model (Akhtar et al, 1982;Corbin et al, 1978). In the only study carried out with the bonnet monkey it was concluded that it fails to respond to the LHRH agonist BA16 des gly 10 LHRH ethylamide (Levitan et al, 1977). However, recently we have demonstrated that the bonnet monkey is quite responsive to GnRH or its analogues as judged by increase in the serum testosterone (Jagannadha Rao et al, 1984).…”
Section: Discussionmentioning
confidence: 99%